2022
DOI: 10.3389/fmolb.2022.843814
|View full text |Cite
|
Sign up to set email alerts
|

Identification of SNAT Family Genes Suggests GhSNAT3D Functional Reponse to Melatonin Synthesis Under Salinity Stress in Cotton

Abstract: Serotonin N-acetyltransferase (SNAT) is a key enzyme in the biosynthesis of melatonin, and plays an important role in the regulation of melatonin synthesis. The study of SNAT is of great significance to understand the function of melatonin. In this study, we analyzed the structural characteristics, phylogenetic relationship, gene structure, expression pattern, evolutionary relationship and stress response of the members of the SNAT gene family in upland cotton through bioinformatics. A putative Serotonin n-ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…The determination of Ca 2+ content was performed according to the method we reported previously [ 38 ]. The detection of NO and proline contents and SOD activity were performed by using the nitric oxide (NO) assay kit, proline assay kit and superoxide dismutase (SOD) activity assay kit (Nanjing Jiancheng Bioengineering Institute, Nanjing, China), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The determination of Ca 2+ content was performed according to the method we reported previously [ 38 ]. The detection of NO and proline contents and SOD activity were performed by using the nitric oxide (NO) assay kit, proline assay kit and superoxide dismutase (SOD) activity assay kit (Nanjing Jiancheng Bioengineering Institute, Nanjing, China), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, collinearity analysis showed that a large number of tandem repeats occurred between homologous chromosomes. These results suggest that modes of gene family expansion, including duplication, and multiple gene copies prevent gene mutation-induced gene function loss, which indicates the importance of their function ( Xu et al., 2012 ; Zhang et al., 2022 ). Among these genes, GhSBT26 and GhSBT27A are tandemly repeated genes.…”
Section: Discussionmentioning
confidence: 84%
“…The GhGAD protein interaction network was analyzed through the STRING database ( https://string-db.org/ ) ( Zhang et al, 2022 ). On the basis of A. thaliana orthologs to predict the interaction of GhGAD family genes with other genes in cotton.…”
Section: Methodsmentioning
confidence: 99%